2018
DOI: 10.1159/000495319
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome Sequencing Analysis Reveals Role of miR-138-5p/ TBL1X in Placenta from Gestational Diabetes Mellitus

Abstract: Background/Aims: The placenta has been suggested to play a crucial role in the pathology of gestational diabetes mellitus (GDM). Placenta-specific microRNAs (miRNAs) and the corresponding targeting genes involved in the pathology of GDM still remain to be elucidated. We aimed to identify the dysregulated miRNAs and the corresponding mRNA targets through an integrated miRNA and mRNA transcriptomic profiles analysis and investigate the role of differentially expressed miR-138-5p/TBL1X in GDM. Methods: RNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Analysis of the circulating miRNA profiles in peripheral blood has revealed that miR-1275, miR-16-5p, miR-17-5p, miR-19a-3p, miR-19b-3p, miR-20a-5p, miR-195-5p and miR-3664-3p are significantly upregulated in GDM pregnancies compared with those in normal pregnancies. In contrast, miR-29a, miR-132, miR-142-5p, miR-222 and miR-4666a-3p were found to be downregulated in women affected by GDM [51][52][53][54][55][56][57]. RNA sequencing has revealed that miR-138-5p is significantly downregulated in GDM placentas [53].…”
Section: Peripheral Blood Exosomes and Circulating Mirnas In Gestatiomentioning
confidence: 97%
See 1 more Smart Citation
“…Analysis of the circulating miRNA profiles in peripheral blood has revealed that miR-1275, miR-16-5p, miR-17-5p, miR-19a-3p, miR-19b-3p, miR-20a-5p, miR-195-5p and miR-3664-3p are significantly upregulated in GDM pregnancies compared with those in normal pregnancies. In contrast, miR-29a, miR-132, miR-142-5p, miR-222 and miR-4666a-3p were found to be downregulated in women affected by GDM [51][52][53][54][55][56][57]. RNA sequencing has revealed that miR-138-5p is significantly downregulated in GDM placentas [53].…”
Section: Peripheral Blood Exosomes and Circulating Mirnas In Gestatiomentioning
confidence: 97%
“…In contrast, miR-29a, miR-132, miR-142-5p, miR-222 and miR-4666a-3p were found to be downregulated in women affected by GDM [51][52][53][54][55][56][57]. RNA sequencing has revealed that miR-138-5p is significantly downregulated in GDM placentas [53]. A recent study reported that ten exosomal miRNAs in serum were present at significantly higher levels in GDM cases than in controls [56].…”
Section: Peripheral Blood Exosomes and Circulating Mirnas In Gestatiomentioning
confidence: 99%
“…Ding et al uncovered a set of deregulated microRNAs by RNA sequencing and further qRT-PCR validation in placental tissues from eight GDM women compared to eight CTRLs [114]. An integrative evaluation of microRNA and mRNA expression was performed and the predicted biological functions of the differentially expressed microRNA and mRNA were related to placenta morphology and development.…”
Section: Short-term Complicationsmentioning
confidence: 99%
“…Despite years of investigation, very little is known about the genetic predisposition for gestational diabetes mellitus (GDM). Increasing number of studies have reported pathological changes of placenta tissues in gestational diabetes mellitus (GDM), while the underlying mechanisms involved in this process are still largely uncertain [12, 13]. We herein tried to identify the genetic variation of placenta involving GDM currencies by the cell-free DNA in the maternal plasma, which was proved to be derived from placental trophoblast cells [14, 15].…”
Section: Resultsmentioning
confidence: 99%